Effects of sex and estrous cycle on intravenous oxycodone self-administration and the reinstatement of oxycodone-seeking behavior in rats - Hinds, Nicole M.; Wojtas, Ireneusz D.; Gallagher, Corinne A.; Corbett, Claire M.; Manvich, Daniel F. (Frontiers in Behavioral Neuroscience, 2023)
The increasing misuse of both prescription and illicit opioids has culminated in a national healthcare crisis in the United States. Oxycodone is among the most widely prescribed and misused opioid pain relievers and has been associated with a high risk for transition to compulsive opioid use. Here, we sought to examine potential sex differences and estrous cycle-dependent effects on the reinforcing efficacy of oxycodone, as well as on stress-induced or cue-induced oxycodone-seeking behavior, using intravenous (IV) oxycodone self-administration and reinstatement procedures. In experiment 1, adult male and female Long-Evans rats were trained to self-administer 0.03 mg/kg/inf oxycodone according to a fixed-ratio 1 schedule of reinforcement in daily 2-hr sessions, and a dose-response function was subsequently determined (0.003-0.03 mg/kg/inf). In experiment 2, a separate group of adult male and female Long-Evans rats were trained to self-administer 0.03 mg/kg/inf oxycodone for 8 sessions, followed by 0.01 mg/kg/inf oxycodone for 10 sessions. Responding was then extinguished, followed by sequential footshock-induced and cue-induced reinstatement tests. In the dose-response experiment, oxycodone produced a typical inverted U-shape function with 0.01 mg/kg/inf representing the maximally effective dose in both sexes. No sex differences were detected in the reinforcing efficacy of oxycodone. In the second experiment, the reinforcing effects of 0.01-0.03 mg//kg/inf oxycodone were significantly attenuated in females during proestrus/estrus as compared to metestrus/diestrus phases of the estrous cycle. Neither males nor females displayed significant footshock-induced reinstatement of oxycodone seeking, but both sexes exhibited significant cue-induced reinstatement of oxycodone seeking at magnitudes that did not differ either by sex or by estrous cycle phase. These results confirm and extend previous work suggesting that sex does not robustly influence the primary reinforcing effects of oxycodone nor the reinstatement of oxycodone-seeking behavior. However, our findings reveal for the first time that the reinforcing efficacy of IV oxycodone varies across the estrous cycle in female rats.